Generalized Problematic Internet Use Scale 2: Adaptation for adults from Buenos Aires - Stover, Juliana Beatriz (2023)
The Generalized Problematic Internet Use Scale 2 was adapted for the adult population of Buenos Aires. Participants were 225 subjects (68.4% female; 30.7% male, 0.9% non-binary). Instruments administered were: survey of sociodemographic data and characteristics of use of social networks; Generalized Problematic Internet Use Scale 2; Mental Health Continuum Short Form and; Symptom Check List-27. Confirmatory factor analysis was carried out; It was found an adequate fit of the structure proposed by the original author. Cronbach’s and ordinals alphas ranged from .77 to .87. Significant positive correlations were found between the generalized problematic use of the Internet, the psychopathological symptoms and the time of use of social media. Associations were negative with psychological well-being.